4-Hydroxy-3-methylbenzofuran-2-carbohydrazones as novel LSD1 inhibitors. Issue 10 (15th May 2020) - He, Xingrui; Gao, Yuan; Hui, Zi; Shen, Guodong; Wang, Shuo; Xie, Tian; Ye, Xiang-Yang
Graphical abstract: Abstract: Histone lysine specific demethylase 1 (LSD1 or KDM1A) is a potential therapeutic target in oncology due to its overexpression in various human tumors. We report herein a new class of benzofuran acylhydrazones as potent LSD1 inhibitors. Among the 31 compounds prepared, 14 compounds exhibited excellent LSD1 inhibitory activity with IC50 values ranging from 7.2 to 68.8 nM. In cellular assays, several compounds inhibited the proliferations of various cancer cell lines, including PC-3, MCG-803, U87 MG, PANC-1, HT-29 and MCF-7. This opens up the opportunity for further optimization and investigation of this class compounds for potential cancer treatment.